The 4AT scale for rapid detection of delirium in emergency department triage - Soler-Sanchis, Angela; Martínez-Arnau, Francisco Miguel; Sánchez-Frutos, José; Pérez-Ros, Pilar (Frontiers in Medicine, 2024)
Aims To assess the diagnostic accuracy and time impact of the 4AT scale in emergency department triage. Methods A Prospective diagnostic accuracy study was carried out. People aged ≥65 years presenting to the emergency department from 1 November 2021 to 30 June 2022 were included. Nurses opportunistically screened eligible patients using the 4AT scale during triage according to the Manchester Triage System Francesc de Borja Hospital emergency department, Gandía (Spain). Accuracy was compared with medical diagnosis of delirium. Time (seconds) spent in triage with and without screening was assessed. Results The study included 370 patients (55.1% men, mean age 81.8 years), of whom 58.4% (n = 216) were screened. A final diagnosis of delirium was made in 41.4% of those screened. The most frequently used presentational flow charts and discriminators were ‘behaving strangely’ (15%) and ‘rapid onset’ (33.3%). The highest accuracy was obtained for a score of 3 points or more (sensitivity 85.1%; specificity 66.9%; positive predictive value 52.8%; negative predictive value 71.7%). No significant differences were found in the time spent in triage according to the performance of screening. Conclusion A score of 3 points or more on the 4AT scale enables rapid detection of delirium in emergency department triage, without consuming more time than conventional triage.